2005
DOI: 10.1007/s11104-005-5399-x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial communities associated with the rhizosphere of transgenic Bt 176 maize (Zea mays) and its non transgenic counterpart

Abstract: The effect of transgenic Bt 176 maize on the rhizosphere bacterial community has been studied with a polyphasic approach by comparing the rhizosphere of Bt maize cultivated in greenhouse with that of its non transgenic counterpart grown in the same conditions. In the two plants the bacterial counts of the copiotrophic, oligotrophic and sporeforming bacteria, and the community level catabolic profiling, showed no significant differences; differences between the rhizosphere and bulk soil bacterial communities we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
71
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 45 publications
13
71
0
5
Order By: Relevance
“…However, another comparison of samples from Bt and non-Bt maize fields revealed a lower abundance of nematodes in Bt fields (Griffiths et al, 2005). The compositions of bacterial communities (Devare et al, 2004;Baumgarte and Tebbe, 2005) and the relative abundances of bacterial classes (Brusetti et al, 2004) did not differ among Bt and non-Bt treatments. It should be noted that Brusetti et al (2004) found no difference in the abundance of spore forming bacteria, which includes Bacillus entomopathogens.…”
Section: Entomopathogensmentioning
confidence: 83%
See 1 more Smart Citation
“…However, another comparison of samples from Bt and non-Bt maize fields revealed a lower abundance of nematodes in Bt fields (Griffiths et al, 2005). The compositions of bacterial communities (Devare et al, 2004;Baumgarte and Tebbe, 2005) and the relative abundances of bacterial classes (Brusetti et al, 2004) did not differ among Bt and non-Bt treatments. It should be noted that Brusetti et al (2004) found no difference in the abundance of spore forming bacteria, which includes Bacillus entomopathogens.…”
Section: Entomopathogensmentioning
confidence: 83%
“…The compositions of bacterial communities (Devare et al, 2004;Baumgarte and Tebbe, 2005) and the relative abundances of bacterial classes (Brusetti et al, 2004) did not differ among Bt and non-Bt treatments. It should be noted that Brusetti et al (2004) found no difference in the abundance of spore forming bacteria, which includes Bacillus entomopathogens. Protozoa and fungi are also unaffected by some commercialized Bt crops (Saxena and Stotzky, 2001a).…”
Section: Entomopathogensmentioning
confidence: 87%
“…In this respect, Widmer (2007) suggested that effects observed on symbiotic microorganisms will only be disadvantageous for the crop itself, without representing a concern for the ecosystem. In addition, a number of other studies (reviewed by Widmer, 2007;Filion, 2008;, performed under laboratory, glasshouse or field conditions covering a large array of classical and more recent analytical tools, revealed only some minor changes in soil microbial community structure with Bt-maize compared to non-Bt-maize (Blackwood and Buyer, 2004;Brusetti et al, 2004;Griffiths et al, 2006;Mulder et al, 2006) or generally show no adverse effects of the Cry1Ab protein released by Bt-maize in root exudates or from biomass incorporated into soil microorganisms or microorganism-mediated processes (Saxena and Stotzky, 2001a;Flores et al, 2005;Anonymous, 2006;Hönemann et al, 2008;. Where effects on microbial communities have been reported, these effects were in general considered spatially and temporally limited, and small compared with those induced by differences in geography, temperature, seasonality, plant variety and soil type (Fang et al, 2005(Fang et al, , 2007Griffiths et al, 2005Griffiths et al, , 2006Lilley et al, 2006;Filion, 2008;.…”
Section: Effects On Human and Animal Healthmentioning
confidence: 99%
“…In this respect, Widmer (2007) suggested that effects observed on symbiotic microorganisms living in close association with crops will only be disadvantageous for the crop itself, without representing a concern for the ecosystem. In addition, a number of other studies (reviewed by Widmer, 2007 and, performed under laboratory, glasshouse and field conditions and covering a large array of classical and more recent analytical tools, revealed only some minor changes in soil microbial community structure with Bt-maize compared to non-Bt-maize (Blackwood and Buyer, 2004;Brusetti et al, 2004;Mulder et al, 2005;Griffiths et al, 2006) or generally show no adverse effects of the Cry1Ab protein released by Bt-maize in root exudates or from biomass incorporated into soil on microorganisms or microorganism-mediated processes (Saxena and Stotzky, 2001a;Flores et al, 2005;StMUGV, 2006;Hönemann et al, 2008;. In studies were effects on microbial communities have been reported, these effects were in general considered spatially and temporally limited, and small compared with those induced by differences in geography, temperature, seasonality, plant variety or soil type (Fang et al, 2005(Fang et al, , 2007Griffiths et al, 2005Griffiths et al, , 2006Lilley et al, 2006;.…”
Section: Gmo Panel Assessmentmentioning
confidence: 99%